The use of NH4+ rather than NO3- affects cell stoichiometry, C allocation, photosynthesis and growth in the cyanobacterium Synechococcus sp. UTEX LB 2380, only when energy is limiting - Ruan, Zuoxi; Giordano, Mario (Plant, cell & environment, 2017)
The assimilation of N-NO3- requires more energy than that of N-NH4+ . This becomes relevant when energy is limiting and may impinge differently on cell energy budget depending on depth, time of the day and season. We hypothesize that N-limited and energy-limited cells of the oceanic cyanobacterium Synechococcus sp. differ in their response to the N source with respect to growth, elemental stoichiometry and carbon allocation. Under N limitation, cells retained almost absolute homeostasis of elemental and organic composition, and the use of NH4+ did not stimulate growth. When energy was limiting, however, Synechococcus grew faster in NH4+ than in NO3- and had higher C (20%), N (38%) and S (30%) cell quotas. Furthermore, more C was allocated to protein, whereas the carbohydrate and lipid pool size did not change appreciably. Energy limitation also led to a higher photosynthetic rate relative to N limitation. We interpret these results as an indication that, under energy limitation, the use of the least expensive N source allowed a spillover of the energy saved from N assimilation to the assimilation of other nutrients. The change in elemental stoichiometry influenced C allocation, inducing an increase in cell protein, which resulted in a stimulation of photosynthesis and growth.
Keywords: amoniové sloučeniny; sacharidy; Nitrates; nitrogen; Nitrogen; FTIR; Biomass; fosfor; bakteriální proteiny; lipidy; Bacterial Proteins; energetický metabolismus; síra; Photosynthesis; Energy Metabolism; cyanobacteria; Carbohydrates; adenosintrifosfát; Lipids; fotosyntéza; energy; Ammonium Compounds; Adenosine Triphosphate; Phosphorus; Oxygen; carbon allocation; dusičnany; Synechococcus; Carbon; biomasa; uhlík; elemental stoichiometry; dusík; kyslík; Sulfur